On improving training mechanisms teaching staff and prospects for targeted learning in the interests of universities - S. A. Kudzh; N. B. Golovanova (Российский технологический журнал)
The article reveals the main trends and staffing impediments in higher educational institutions based on the analysis of legislation and standards, academic literature, statistics and the available management experience of educational activities in engineering training areas. The targeted training attributes as a framework for vocational training management are also specified in the paper.Shortage of academic staff capable to use the efficient advanced technologies for rebuilding the training process quickly under changing both labor market environment and students’ interests is one of the main factors that today compromises the quality of highly qualified personnel training for the national economy causing serious concern of higher education authorities and educational institutions administration. The lack of interest of academic staff to conduct scientific researches due to on the one hand, by the increased competition for grants, targeted subsidies for fundamental and applied research and the inability (lack of skills) of many applicants to apply for funding correctly and timely, on the other hand contributes to low indicators of the research activities.The authors have concluded that the targeted training, which allows organizing the training process for young professionals starting from high school graduates, could be the main framework for recruiting them to teaching and researching positions that is undoubtedly to the benefit of an educational institution.